Manipulation of DHPS activity affects dendritic morphology and expression of synaptic proteins in primary rat cortical neurons - Cavalli, Paola; Raffauf, Anna; Passarella, Sergio; Helmuth, Martin; Dieterich, Daniela C.; Landgraf, Peter (Frontiers in Cellular Neuroscience, 2024)
Deoxyhypusine synthase (DHPS) catalyzes the initial step of hypusine incorporation into the eukaryotic initiation factor 5A (eIF5A), leading to its activation. The activated eIF5A, in turn, plays a key role in regulating the protein translation of selected mRNAs and therefore appears to be a suitable target for therapeutic intervention strategies. In the present study, we analyzed the role of DHPS-mediated hypusination in regulating neuronal homeostasis using lentivirus-based gain and loss of function experiments in primary cortical cultures from rats. This model allows us to examine the impact of DHPS function on the composition of the dendritic and synaptic compartments, which may contribute to a better understanding of cognitive function and neurodevelopment in vivo. Our findings revealed that shRNA-mediated DHPS knockdown diminishes the amount of hypusinated eIF5A (eIF5AHyp), resulting in notable alterations in neuronal dendritic architecture. Furthermore, in neurons, the synaptic composition was also affected, showing both pre- and post-synaptic changes, while the overexpression of DHPS had only a minor impact. Therefore, we hypothesize that interfering with the eIF5A hypusination caused by reduced DHPS activity impairs neuronal and synaptic homeostasis.